Technology and Economic Analysis of Sewage Source Heat Pump Combined Type District Heating Method. (December 2017) - Qunli, Zhang; Qian, Nie; Fang, Liu; Chaohui, Yin
Abstract: This paper puts forward a kind of compound district heating method for* recycling waste heat of wasting water for building heat supply. The way is to the sewage treatment plant and the district heating plant in combination with heating operation, through the sewage source heat pump system for recycling the sewage heat energy for urban heating system returns water preheating. Research results show that compared with the other two heating methods, under the same heat loading, the sewage source heat pump combined type district heating method has the advantages of high energy consumption, low operation cost, distance from heating and good suitability.